2000
DOI: 10.1159/000029459
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Alpha-2-Macroglobulin, Alpha-1-Acid Glycoprotein, and C-Reactive Protein in Pleural Effusion Differentiation

Abstract: Background: The differentiation between exudates and transudates is fundamental when investigating the cause of pleural effusions. Acute-phase proteins could be potentially useful markers in this discrimination. Objective: The present study was designed to evaluate whether the acute-phase proteins: α2-macroglobulin (AMG), α1-acid glycoprotein (AAG) and C-reactive protein (CRP) are useful in investigating the pleural effusions. Methods: We prospectively measured the concentrations of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 20 publications
1
15
0
1
Order By: Relevance
“…Previous studies on CRP in pleural fluid concluded that this parameter may differentiate transudates from exudates, but with worse results than those of classical tests [23,24,25]. In one study [23], the authors found that CRP levels were significantly higher in parapneumonic and tuberculous effusions, and our group [14] reported previously that in pleural exudates a CRP <20 mg/l suggests a malignant origin, whereas a level >45 mg/l virtually ruled out this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on CRP in pleural fluid concluded that this parameter may differentiate transudates from exudates, but with worse results than those of classical tests [23,24,25]. In one study [23], the authors found that CRP levels were significantly higher in parapneumonic and tuberculous effusions, and our group [14] reported previously that in pleural exudates a CRP <20 mg/l suggests a malignant origin, whereas a level >45 mg/l virtually ruled out this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of studies on various novel markers, such as acute phase proteins [55], oncogenes [56], cytokines involved in inflammation [57, 58], and matrix metalloproteinases [59], in the differential diagnosis between transudates and exudates and/or between malignant and benign pleural effusions. Although some may be adequate markers for pleural effusion differentiation, they are not as sensitive, specific, or cost- and time-efficient as the easily available standard tests [60].…”
Section: Other Markersmentioning
confidence: 99%
“…Several tumor markers and biochemical parameters have been proposed in an effort to improve the differential diagnosis of pleural effusion [12, 13, 14, 15, 16]. Some of them, such as cholesterol levels, seem to reflect the etiology of pleural infusions [13, 14, 15, 16, 17]. …”
Section: Introductionmentioning
confidence: 99%